Significant Lightning Stroke Count in Negative Ground Flashes Featuring the Relationship of Preliminary Breakdown and The First Return Stroke - Isa, Nur Asyiqin; Baharudin, Zikri Abadi; Zainuddin, Hidayat (International Journal of Integrated Engineering, 2023)
The separation duration of Preliminary Breakdown to the first Return Stroke (PB-RS duration) and the ratio between the highest amplitude pulse of Preliminary Breakdown and the first Return Stroke pulse (PB/RS ratio) have become parameters for determining the relationship between lightning ground flashes with physical changes such as the latitude effect, regional and thunderstorm successfully by many researchers. This paper presents a novel finding for determining the occurrences of a lightning strike or stroke count in a negative ground flash with a duration of two seconds by using the primary tool mentioned above. Stroke count information in a lightning ground flash is crucial for power circuit breaker settings for power system protection. In this present study, 83 broadband radiation electric fields (or fast fields) gathered using a 12-bit high-speed transient recorder (HDO 4024) with a resolution of tens of nanoseconds and 12.5 MS/s. Interestingly, the PB/RS ratio with similar latitudes is consistent despite different monsoon measurements. The PB-RS duration, on the other hand, has two factors longer during the Southwest monsoon than during the Northeast monsoon. The weak pulses train (100). By providing the significant stroke count under different variations of Northeast monsoon, this study allows power engineers to decide the significant parameter set up in the circuit breaker system. However, it would be more remarkable if one could provide bulky data for this specific study.